2012
DOI: 10.3390/f3020317
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Prescribed Fire Frequency on Coarse Woody Debris Volume, Decomposition and Termite Activity in the Longleaf Pine Flatwoods of Florida

Abstract: Longleaf pine (Pinus palustris) ecosystems have been reduced dramatically throughout their range. Prescribed burning is considered the best way to restore and maintain plant communities associated with longleaf pine, but little is known about its effects on coarse woody debris and associated organisms. We conducted a 5-year study on the Osceola National Forest in northeastern Florida to determine how dormant-season prescribed burns at different frequencies (annual, biennial, quadrennial or unburned) applied ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
5
16
1
Order By: Relevance
“…Despite the substantial changes that occur to above-ground vegetation following fire in mallee ecosystems [ 3 ], fire history (time since fire) had no effect on any termite species or on termite richness, in any vegetation type. This finding lends support to recent studies which have concluded that termites generally are resilient to fire when considered over long time periods [ 26 , 55 , 56 ]. One explanation for the lack of response to fire in this study concerns the ecological traits of the species in our study region.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the substantial changes that occur to above-ground vegetation following fire in mallee ecosystems [ 3 ], fire history (time since fire) had no effect on any termite species or on termite richness, in any vegetation type. This finding lends support to recent studies which have concluded that termites generally are resilient to fire when considered over long time periods [ 26 , 55 , 56 ]. One explanation for the lack of response to fire in this study concerns the ecological traits of the species in our study region.…”
Section: Discussionsupporting
confidence: 90%
“…This is a higher rate than reported for pine elsewhere in the southeastern United States (Barber and Van Lear 1984, Eaton and Sanchez 2009, Hanula et al 2012, Mobley et al 2013). Although differences in site conditions and bolt lengths are likely important variables, this discrepancy is probably due in part to our use of initial volume (Ulyshen and Wagner 2013), as opposed to final water displaced volume when calculating specific gravity.…”
Section: Discussioncontrasting
confidence: 41%
“…This species was previously reported to be associated with heartwood hollows in Amazonian forest trees [42,43], but at low frequencies [26]. Species of Reticulitermes, another member of the Rhinotermitidae, and other species of Coptotermes are reportedly common colonizers of the heartwoods of urban trees and trees in forests subjected to prescribed burns [59,60]. The Formosan subterranean termite, C. formosanus, which is considered an urban pest, for instance, was present in 37 and 52% of forest fragments near two urban areas in Southeastern USA [28].…”
Section: Discussionmentioning
confidence: 93%